Ride with the devil - Copyright Collection (Library of Congress) (United States : USA Films, 1999)
Jake Roedel and Jack Bull Chiles are friends in Missouri during the Civil War.
Copyright: Universal City Studios, Inc. DCR 1998; PUB 15Oct99; REG 27Jan00; PA965-427.
Summary taken from Internet movie database.
Digital sound track (DTS) on 2 compact disc (serial no. 1904) stored in 1 film can CGC 9322.
Sources used: copyright data base; Internet movie database, 9/06/2001.
Skeet Ulrich, Tobey Maguire, Jewel Kilcher, Jeffrey Wright, Simon Baker.
Keywords: Adventure -- Feature